HYPOGLYCEMIC EFFECTS OF BARLERIA NOCTIFLORA FRACTIONS ON HIGH FAT FED WITH LOW DOSE STREPTOZOTOCIN INDUCED TYPE-2 DIABETES IN RATS - Arumugam, Suresh; Natesan, Senthilkumar (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To investigate in vitro and in vivo antidiabetic activity of Barleria noctiflora (B. noctiflora) fractions on high-fat diet (HFD) with low dose Streptozotocin (STZ) induced type-2 diabetes in rats. Methods: B. noctiflora were successively extracted and then fractionated by Ethyl acetate and n. butanol. The in vitro antidiabetic activity from Î±-amylase and Î±-glucosidase was used to evaluate the potential activity of the fractions. The in vivo antidiabetic activity is evaluated against HFD/STZ induced type-2 diabetic in rats at a dose of 100 mg/kg, 200 mg/kg and 400 mg/kg, p. o for 28days. Results: Ethyl acetate fraction of B. noctiflora (EAFBN) showed the highest antidiabetic activity and IC50 values of Î±-amylase inhibition (114.7Â±0.15) and Î±-glucosidase inhibition (104.93Â±0.28) than other fraction. In HFD/STZ (40 mg/kg) diabetic rats the EAFBN showed a dose dependent significant hypoglycemic property from body weight, blood glucose, serum lipids, serum cholesterol, serum triglycerides, urea, creatinine, hepatic enzymes and liver glycogen levels. The EAFBN significantly (P<0.01) increase the level of serum insulin. Histologically, focal necrosis was observed in the diabetic rat pancreas; however, was less obvious in treated groups. Conclusion: The EAFBN is a potent hypoglycemic agent and beneficial in reducing the elevated blood glucose level, improve the lipid profile and insulin level and histopathological changes in the pancreas of HFD/STZâ€induced nonâ€genetic rat model of type-2 diabetes mellitus. <!–[if gte vml 1]> <![endif]–><!–[if !vml]–> <!–[endif]–>